Mangrove Density Mapping for Sustainable Utilization and Management in Klawalu Mangrove Tourism Park, Sorong City - Pattiasina, Thomas Frans; Tjolli , Ihwan; Bless, Aplena Ellen; Lekitoo, Krisma (Universitas Brawijaya, 2023)
Data and information on resource utilization supported by vegetation mapping are the basis for developing a sustainable mangrove management strategy. This study aims to map the vegetation density and identify the use of mangroves by the community in the Klawalu Mangrove Tourism Park (Taman Wisata Mangrove Klawalu-TWMK) Sorong City. The satellite imagery used is Sentinel 2A level 1C. Image pre-processing includes atmospheric correction, geometric correction and image cropping. Determination of the extent and distribution of mangrove vegetation is carried out by applying the color composite method and mangrove boundary delineation. Mangrove vegetation density mapping was carried out by applying the Normalized Difference Vegetation Index (NDVI) method. Identification of the species and intensity of mangrove utilization was carried out through observation and interviews with respondents who were determined purposively. Based on the results of the analysis, the total area of mangrove vegetation in TWMK and its mapped surroundings is 144.64 ha. Of this area, 69.01 ha (47.71%) is classified as very dense, 34.96 ha (24.17%) is classified as dense, and 24.23 ha (16.75%) is classified as moderate, 12. 94 ha (8.95%) is classified as sparse, and 3.5 ha (2.42%) is classified as very sparse. The intensity of resource utilization from the mangrove ecosystem is quite high, especially the utilization of mangrove wood and coral mining. Awareness/education efforts need to be continued, as well as alternative livelihood solutions to reduce the heavy dependence on mangrove resources.